Fakultas Tarbiyah dan Ilmu Keguruan Mengajar: Menginspirasi Generasi Muda untuk Cinta Bahasa Arab - Aniati, Ira; Suci Meliani; Hurriyatus Sa’adiyah (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
The issue of low student interest in learning Arabic is still prevalent in elementary schools today, particularly among students at MDTA Nurul Iman Sihitang. To address this, the Faculty of Tarbiyah and Teacher Training at UIN SYAHADA Padangsidimpuan launched the